Pengaruh Proporsi Tepung Terigu, Tepung Tempe Dan Tepung Daun Kelor (Moringa oliefera) Terhadap Mutu (Protein Dan Zat Besi) Dan Daya Terima Mie Basah - Yuliana Salman; Sari Novita; Adi Burhanudin; STIKES Husada Borneo; Poltekkes Kemenkes Banjarmasin; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2016)
Nutritional problems are the exist problems in every country, particularly Indonesia unfinished controlled is malnutrition and anemia. The high prevalence of short adolescents with percentages as much as 31,2% and the prevalence of adolescents with the percentage of 8,9%. While adolescent pravelensi anemia for girls is 23,9% and that 23,9% of young men. Tempe flour has a sweet flavor. However, the protein content remains high. Moringa leaf flour is flour which contains more iron than spinach and is suitable for the replacement of wheat flour. This study aims to determine the percentage of wheat flour, soybean meal and flour of Moringa leaves on the quality (protein and iron) and wet noodle acceptance (color, aroma, texture and taste). This study is an experiment with a completely randomized design (CRD) with four treatments and three replicates. Test methods for the protein content is Kjedahl. Test Method Iron is titration. Data analysis is the one-way ANOVA. Results showed no effect of flour, soy flour and Moringa leaves the protein content of wet noodles (p = 0.088), while the levels of iron there is no influence of the percentage of flour, soy flour and moringa leaves wet noodles 9 (p = 0,134). There is an influence on the color test (p = 0.000), aroma (p = 0,000), and texture (p = 0,009).